2011
DOI: 10.1139/w11-095
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of synonymous codon usage inShigella flexneri2a strain 301 and otherShigellaandEscherichia colistrains

Abstract: In this study, we analysed synonymous codon usage in Shigella flexneri 2a strain 301 (Sf301) and performed a comparative analysis of synonymous codon usage patterns in Sf301 and other strains of Shigella and Escherichia coli. Although there was a significant variety in codon usage bias among different Sf301 genes, there was a slight but observable codon usage bias that could primarily be attributable to mutational pressure and translational selection. In addition, the relative abundance of dinucleotides in Sf3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 43 publications
2
5
0
Order By: Relevance
“…In this study, we found that, roughly similar to other RNA viruses, such as Ebolavirus (mean ENC = 57.23) , Bovine viral diarrhea virus (mean ENC = 51.43) , West Nile virus (mean ENC = 53.81) , the ENC values for HYSV were high (mean ENC = 51.11 > 40), indicating that the overall extent of codon usage bias in HYSV genomes is low. In fact, the previous results published by Jenkins et al had shown that the overall extent of codon usage bias in RNA viruses was low.…”
Section: Discussionsupporting
confidence: 50%
See 3 more Smart Citations
“…In this study, we found that, roughly similar to other RNA viruses, such as Ebolavirus (mean ENC = 57.23) , Bovine viral diarrhea virus (mean ENC = 51.43) , West Nile virus (mean ENC = 53.81) , the ENC values for HYSV were high (mean ENC = 51.11 > 40), indicating that the overall extent of codon usage bias in HYSV genomes is low. In fact, the previous results published by Jenkins et al had shown that the overall extent of codon usage bias in RNA viruses was low.…”
Section: Discussionsupporting
confidence: 50%
“…To further establish mutational bias or translational selection in HYSV can explain their codon usage, first, the G þ C content at the first and second codon positions (GC 12 ) were compared with that at synonymous third codon positions (GC 3 ). It was found that GC 12 and GC 3 were significantly correlated (r ¼ À0.404, p < 0.01). This suggests that they are most likely the result of mutational bias, as natural selection would be selected to act differently on different codon positions.…”
Section: Gc 3 Gc12mentioning
confidence: 95%
See 2 more Smart Citations
“…The mitochondrial genome often accumulates nucleotide substitutions at faster rates than does the nuclear genome, especially for mammalian mitochondrial DNA (Brown et al, 1979;Martin et al, 1992;Ramirez et al, 1993). Various studies have analyzed different organisms, such as viruses (Zhang et al, 2011), bacteria (Luo et al, 2011), yeast (Whittle et al, 2011), plants , and animals (Musto et al, 2001;Fadiel et al, 2002). However, codon usage in platyhelminth mitochondrial genomes has only rarely been studied.…”
Section: Introductionmentioning
confidence: 99%